Ebstein's anomaly. Genetic study of 26 families. - Emanuel, R (1976)
The families of 26 patients with Ebstein's anomaly were examined. There were 120 first-degree relatives, 100 of whom were living, and 93 of these were examined. Information was available on 14 of the 20 who had died. No case of Ebstein's anomaly was found among the first-degree relatives, but 2 had ventricular septal defects and another, who died at 7 months, was said to have had congenital heart disease. In more distant relatives there were 6 with congenital heart disease, including 2 with ventricular septal defects and 2 with Fallot's tetralogy.